2021
DOI: 10.1111/eje.12722
|View full text |Cite
|
Sign up to set email alerts
|

Effect of training on time efficiency and marginal adaptation of computer‐aided design/computer‐aided manufacturing crowns among dental students

Abstract: Introduction The computer‐aided design/computer‐aided manufacturing (CAD/CAM) technology has revolutionised dentistry at present. An operator's skills can affect the overall clinical duration and marginal accuracy of the prosthesis fabricated through this workflow. The aim of this study was to assess the effect of CAD/CAM hands‐on training compared with that of a self‐instructional video on the performance of dental students in digital impression and fabrication of a CAD/CAM crown. Methods In this cross‐sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In addition to the contribution of the digital carving exercise to enhancing the students’ ability to carve wax, our data provide evidence that the students’ ability to carry out the exercise has grown positively over the course of three academic years. This finding is in line with that of another study that reported significant improvement in the quality of computer‐aided design outcomes produced by undergraduate dental students over time 32 . Two arguments can be made to explain these results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition to the contribution of the digital carving exercise to enhancing the students’ ability to carve wax, our data provide evidence that the students’ ability to carry out the exercise has grown positively over the course of three academic years. This finding is in line with that of another study that reported significant improvement in the quality of computer‐aided design outcomes produced by undergraduate dental students over time 32 . Two arguments can be made to explain these results.…”
Section: Discussionsupporting
confidence: 91%
“…Theories in medical education, such as Ericsson's Deliberate Practice Model, emphasize the significance of instant and constructive feedback in developing students' competence in hands-on learning activities. 32,39 Of note, the participating students in our study extrapolated the potential impact of these support strategies to include promoting their overall well-being, boosting their confidence, and maintaining their self-esteem.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In clinical practice, a scanner's accuracy may also be influenced by individual patient factors, such as the amount of saliva/blood, extent of mouth opening, and oral movements. Additionally, the level of training of the operator affects the accuracy of the scanners 125–127 . Precise and swift measurements are beneficial for obtaining accurate digital impressions 2 .…”
Section: Factors Influencing the Performance Of 3d Imaging Devicesmentioning
confidence: 99%
“…Additionally, the level of training of the operator affects the accuracy of the scanners. [125][126][127] Precise and swift measurements are beneficial for obtaining accurate digital impressions. 2 Common errors include non-linear powder application, inappropriate oral cavity scanner placement, and insufficient data.…”
Section: Factors Influencing Intraoral Scannersmentioning
confidence: 99%